Exactly

akshata19, this is a traditional C trap questions. Seemingly innocent and simple. But vicious if we do not approach with care

Veritas Official ExplanationIn the system of equations above, you need to carefully leverage the given information. If you rearrange the given equation to match the statements, you will see that you can eliminate y and z with each statement alone. Remember: the goal in this problem is not to solve for all of the variables, just x.

For statement (1):

Given equation 3x + 2y +2z = 0

Statement (1) x – y – z = 10

Multiply bottom equation by 2 and combine:

3x + 2y +2z = 0

2x – 2y – 2z = 20

5x = 20 and x = 4 so statement (1) is sufficient.

For statement (2):

Given equation 3x + 2y +2z = 0

Statement (1) x + y + z = -2

Multiply bottom equation by -2 and combine:

3x + 2y +2z = 0

-2x – 2y – 2z = 4

x = 4 so statement (2) is also sufficient. The correct answer is (D).

akshata19 wrote:

I gave one glance at the question and options and marked C - three variables -

three equation required

Then realised

You have to find value only of x

Lesson learned don't rush through qstn even if qstn is from your strong topic

3x + 2y = -2z

3x + 2y + 2z = 0

3x + 2(y+z) =0

If you can express y+z in terms of x or constant

You can find x

1) x – y – z = 10

x+10= y+z

If you plug the value of y+z in original eqtn you get value of x

2) x + y + z = -2

y+z = -x-2

plug the value of y+z in original eqtn you get value of x

Hence answer can be derived using both

Option - D

Posted from my mobile device
_________________

My Best is yet to come!